ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT UKUR KINERJA KEUANGAN PERUSAHAAN PADA PT. GEMA SUNGAI MUSI (TAHUN 2019-2024) - Suciyani, Ridha; Noviardy, Andrian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This study aims to analyze the financial performance of PT. Gema Sungai Musi using financial ratios, consisting of liquidity, solvency, profitability, activity, and profitability ratios. The data used are the company's financial statements for the 2019–2024 period, using a quantitative descriptive approach. The results indicate that the company's liquidity ratios are quite good, as the Current Ratio and Quick Ratio are above the minimum standard. The solvency ratios indicate a relatively controlled debt ratio, with an average Debt to Equity Ratio (DER) of <100%. The profitability and profitability ratios demonstrate the company's ability to generate profits despite year-to-year fluctuations. Meanwhile, the activity ratios indicate the company's relatively stable level of asset management efficiency. Overall, PT. Gema Sungai Musi's financial condition is considered healthy, although improvements are needed to improve asset utilization efficiency and profitability.Keywords: Financial statement analysis, Financial ratios, Financial performance, PT. Gema Sungai Musi